Sistem Rancang Bangun Pendingin Otomatis Ruangan Pergudangan Menggunakan Pengendali PID dan SCADA - Saef Maulana; Yoedo Ageng Suryo (Universitas Islam Raden Rahmat, Malang, 2024)
As we know, today's technological developments are much more rapid than in previous eras. Especially in the field of industrial automation systems. With the rapid growth of technology, one of its functions is to make human work easier by controlling a system automatically. In this article, a method for designing and manufacturing a prototype automatic cooling system for warehouse space using a PID controller is written. The work process in this system is to monitor the temperature in warehouse bagging, this system is controlled using ESP32 and the system controller uses PID while SCADA is used as a monitoring system with DHT11 as a temperature sensor and can also be accessed via the web. With the results of implementing this system, it can make human work easier and more comfortable in carrying out work, especially in closed places.